Pengaruh Profitabilitas Dan Kebijakan Deviden Terhadap Nilai Suatu Perusahaan Yang Bergerak Di Bidang Farmasi Periode 2012 S.D 2019 - Roshy Hilda Kusmawati; Nita Yura Roslina; Roro Endah Kumalasari; Sana Sholihah (Acman: Accounting and Management Journal, 2022)
This study aims to determine and analyze the effect of profitability and dividend policy on company value in the manufacturing sector listed on the Indonesia Stock Exchange. The independent variable X1 in this study is profitability proxied by Return On Equity (ROE). The independent variable X2 is the dividend policy proxied by the Dividend Payout Ratio (DPR). Moreover, the dependent variable Y is company value proxied by Price to Book Value (PBV). in pharmaceutical companies in the 2012-2019 period. The sample was selected using the time series method with 32 financial reports from 2012 to 2019. The data testing technique uses multiple linear regression with a significant alpha level of 5%. The results of the study Y = 248.903 + 164.246 (ROE) – 9.111 (DPR) + ɛ. This study proves that profitability has a significant positive effect on firm value, while dividend policy significantly negatively affects firm value. Therefore, simultaneously profitability and dividend policy affect firm value.